2014
DOI: 10.1016/j.psyneuen.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Post-stress rumination predicts HPA axis responses to repeated acute stress

Abstract: Failure of the hypothalamus-pituitary-adrenal (HPA) axis to habituate to repeated stress exposure is related with adverse health outcomes, but our knowledge of predictors of non-habituation is limited. Rumination, defined as repetitive and unwanted past-centered negative thinking, is related with exaggerated HPA axis stress responses and poor health outcomes. The aim of this study was to test whether post-stress rumination was related with non-habituation of cortisol to repeated stress exposure. Twenty-seven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Data for this article were from a larger research project studying the effects of stress on aging, which had been carried out in the Laboratory for Biological Health Psychology at Brandeis University for over two years (Breines et al, 2014; Gianferante et al, 2014). Participants ranged in age from 18 to 65 years and were recruited from the Brandeis University student population and the Greater Boston area.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this article were from a larger research project studying the effects of stress on aging, which had been carried out in the Laboratory for Biological Health Psychology at Brandeis University for over two years (Breines et al, 2014; Gianferante et al, 2014). Participants ranged in age from 18 to 65 years and were recruited from the Brandeis University student population and the Greater Boston area.…”
Section: Methodsmentioning
confidence: 99%
“…Adaptation (habituation) to repeated stressors can decrease the allostatic load on the body (McEwen, 1998), and some recent studies have suggested that perseverative cognitions after stressors prevent this adaptive response. Post-stress rumination, for example, predicted non-habituation of HPA-axis (cortisol) response to the repeated Trier Social Stress Test on a subsequent day (Gianferante et al, 2014), and ruminators failed to adapt their cardiac responses (blood pressure and heart rate) to a repeated 5-min emotional recall task (Johnson, Lavoie, Bacon, Carlson, & Campbell, 2012). These results might implicate that not only prolonged activation of stress-related responses but 2 G. Kökönyei et al the lack of habituation to repeated stressors also contribute to the adverse effect of rumination on somatic health.…”
mentioning
confidence: 99%
“…For example, higher trait rumination was associated with reduced cortisol reactivity to social-evaluative threat in healthy adults (Zoccola, Dickerson, & Zaldivar, 2008). In contrast to trait rumination, higher state rumination immediately following the TSST is associated with higher acute cortisol responses and with non-habituation of cortisol responses to subsequent stressors (e.g., Gianferante et al, 2014). Taken together, these findings suggest that a relatively stable tendency to ruminate about negative emotions and their causes and consequences without engaging in problem solving (Nolen-Hoeksema, 2012), could contribute to lower cortisol responses in remitted-depressed individuals.…”
Section: Discussionmentioning
confidence: 94%